2019
DOI: 10.1111/ped.13800
|View full text |Cite
|
Sign up to set email alerts
|

Growth in children infected with HIV receiving anti‐retroviral therapy in Vietnam

Abstract: Background: There are currently two markers used to monitor treatment response to anti-retroviral therapy (ART) in HIV-infected children: CD4 T-cell count and HIV viral load; but analysis of these could be challenging in resource-poor countries. The aim of this study was therefore to determine whether change in growth parameters such as weight-for-age Z score (WAZ), height-for-age Z score (HAZ) and body mass index-for-age Z score (BMIZ) is associated with treatment response in HIV-infected children.Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…[8][9][10]12 In a cohort of 266 HIV-infected children with suspected tuberculosis (TB) in four countries (Burkina Faso, Cambodia, Cameroon, and Vietnam), Marcy et al found that TB, young age, CD4 less than 10%, miliary features, and elevated serum transaminases were all independent predictors of mortality. 13 In Vietnam, by the end of 2011, there were 3200 Vietnamese children with HIV/AIDS receiving ART; However, there were a few reports on ART outcomes among HIV-infected children [14][15][16] In a study of 86 children on ART in Hanoi, Vietnam, Pham et al reported that the success rate (plasma HIV-1 viral load <1000 copies/mL) was 79.1% after 2-year follow-up. 14 As far as this author knows, no studies to evaluate long-term ART outcomes for infected-HIV children have been conducted in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10]12 In a cohort of 266 HIV-infected children with suspected tuberculosis (TB) in four countries (Burkina Faso, Cambodia, Cameroon, and Vietnam), Marcy et al found that TB, young age, CD4 less than 10%, miliary features, and elevated serum transaminases were all independent predictors of mortality. 13 In Vietnam, by the end of 2011, there were 3200 Vietnamese children with HIV/AIDS receiving ART; However, there were a few reports on ART outcomes among HIV-infected children [14][15][16] In a study of 86 children on ART in Hanoi, Vietnam, Pham et al reported that the success rate (plasma HIV-1 viral load <1000 copies/mL) was 79.1% after 2-year follow-up. 14 As far as this author knows, no studies to evaluate long-term ART outcomes for infected-HIV children have been conducted in Vietnam.…”
Section: Introductionmentioning
confidence: 99%